Leading report regarding the molecular epidemiology of Taenia hydatigena from Pakistan and global overview of the genetic diversity and population structure of the parasite - Mehmood, Naunain; Muqaddas, Hira; Ashraf, Aqsa; Aslam, Mahnoor; Khan, Maryam; Fatima, Madiha; Qadir, Rahman; Ibenmoussa, Samir; Dawoud, Turki M.; Ullah, Muhammad Irfan; Iqbal, Furhan (Elsevier, 2024)
Cysticercosis, caused by larval stage of Taenia (T.) hydatigena is a disease of veterinary concern which causes major economic losses in livestock sector globally. Although livestock is the most productive part of Pakistan's economy, the epidemiological prevalence and genetic diversity of T. hydatigena has not been studied in great detail. Current study was undertaken for the estimation of the prevalence and genetic diversity of T. hydatigena among the goats and sheep of Multan in South Punjab, Pakistan. A PCR protocol targeting the cytochrome c oxidase subunit 1 (cox1) gene of T. hydatigena revealed an overall prevalence of 31.33 % among the small ruminants with higher prevalence in females (40.86 %) and older age group of >3-≤5 years (40.74 %). A total of 30 isolates were sequenced for partial mitochondrial cox1 gene which yielded 12 haplotypes with a haplotype diversity of 0.798 ± 0.68 and nucleotide diversity of 0.0046 ± 0.00183. A star like configuration was demonstrated in the haplotype network with a centrally positioned haplotype. Neutrality indices like Tajima's D and Fu's Fs were also biased towards negativity, a characteristic which suggests an expanding parasitic population. Moreover, the genetic diversity of T. hydatigena was also computed for the partial cox1 gene sequences available on GenBank, NCBI. A total of 415 sequences were retrieved out of which 142 haplotypes were identified having a haplotype diversity of 0.9150 ± 0.012 coupled with a nucleotide diversity of 0.00830 ± 0.00043. The haplotype profile of T. hydatigena population displayed an absence of a central haplotype, however, considerable genetic variation was ascertained. All the populations except Africa had a high haplotype diversity (>0.9), however, high Fst values were observed for a few populations which elucidated limited gene flow among the populations of Central/East Asia, Middle East, Europe and South Asia.